Joint association of triglyceride glucose index (TyG) and a body shape index (ABSI) with stroke incidence: a nationwide prospective cohort study - Ruiying Zhang; Jianan Hong; Yaoling Wu; Liling Lin; Shuying Chen; Yingxiu Xiao (Cardiovascular Diabetology)
Abstract Background Triglyceride glucose index(TyG) and a body shape index(ABSI) are both independent predictor of stroke incidence or adverse prognosis but these two indicators seldom were combined to predict. The purpose of this study is to evaluate whether the combination of TyG and ABSI better predict the incidence of stroke. Methods Based on the China Health and Retirement Longitudinal Study(CHARLS), 8,257 people aged 45 years and older without stroke were enrolled and followed up to 9 years. Sociodemographic information, health status, physical examination and blood data were collected retrospectively. Cox regressions were to determine the relationship between different groups and stroke incidence, using receiver operating characteristic curves to evaluate the diagnostic value. Meanwhile, subgroup analysis was performed to investigate the prediction performance among different population. Results 672(8.14%) of 8,257 participants had stroke incidence during 9 years. In the adjusted multivariate cox regression model, both TyG and ABSI were still predictors of stroke. The HR of TyG was 1.25(95%CI: 1.06–1.47) and the HR of ABSI was 1.33(95%CI: 1.06–1.68). Restricted cubic spline regression showed the associations between TyG or ABSI and stroke. The combination of TyG and ABSI had the highest diagnostic efficacy(AUC: 0.579, 95%CI: 0.553–0.597), compared to TyG(AUC:0.566, 95%CI: 0.544–0.587) and ABSI(AUC:0.533, 95%CI: 0.524–0.597). Kaplan-Meier curves showed that the highest cumulative stroke incidence was among people with high TyG and ABSI(TyG ≥ 8.5742, ABSI ≥ 0.0852; P < 0.0001), which had the highest HR of stroke incidence(HR:1.64, 95%CI:1.2–2.24). Conclusion The combined prediction of TyG and ABSI had higher clinical value and enabled earlier detection of the stroke in the general population, which could be monitored and intervened to reduce the overall burden of stroke.